The Gut Microbiota of an Individual Varies With Intercontinental Four-Month Stay Between Italy and Nigeria: A Pilot Study - Afolayan, Ayorinde O.; Biagi, Elena; Rampelli, Simone; Candela, Marco; Brigidi, Patrizia; Turroni, Silvia; Ayeni, Funmilola A. (Frontiers in Cellular and Infection Microbiology, 2021)
Despite well-established knowledge of the role of diet and the geographic effect on the gut microbiota of human populations, the temporal dynamics of the individual microbiota profile across changes associated with intercontinental short residence are still far from being understood. This pilot study sought to provide insights into the trajectory of the gut microbiota of an individual during a two-month stay in Italy and a subsequent two-month stay in Nigeria, by 16S rRNA gene sequencing and inferred metagenomics. The gut microbiota underwent massive but temporary changes, both taxonomically and based on predicted functionality. The faecal microbiota associated with the short stay in Italy progressively lost diversity and showed a dominance of Firmicutes, while after returning to Nigeria, the microbial community quickly regained the typical profile, in terms of biodiversity and bacterial signatures of traditional lifestyle, i.e., Prevotella and Treponema. Predicted pathways involved in glycolysis, fermentation, and N-acetylneuraminate degradation were enriched during the subsequent two-month stay in Nigeria, whereas pathways associated with amino acid and peptidoglycan synthesis and maturation became over-represented during a short stay in Italy. Our findings stress the plasticity of the individual gut microbiota even during short-term travel, with loss/gain of taxonomic and functional features that mirror those of the gut microbiota of indigenous people dwelling therein.